Economic growth across Chinese provinces: insearch of innovation-driven gains - Michael Funke; Hao Yu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
In this paper we analyse the impact of R&D on total factor productivity across Chinese provinces. We introduce innovations explicitly into a production function and evaluate their contribution to economic growth in 1993 - 2006. The empirical results highlight the importance and the interaction between local and external research. The evidence indicates that growth in China is not explained simply by factor input accumulation.
URN:NBN:fi:bof-201408072004
Keywords: C14; O47; R11; R12; 330; China; R&D; R&D Spillovers; patents; regional economic growth; semiparametric estimators